Level of Student Knowledge about Obesity in Adolescents at SMA Negeri 3 Mataram - Aulia Amini; Ana Pujianti Harahap; Catur Esty Pamungkas; Siti Mardiyah WD (Jurnal Kebidanan, 2022)
Obesity is a complex disorder of appetite regulation and energy metabolism that is controlled by several specific biological factors. The prevalence of obesity in several Southeast Asian countries shows a high percentage. Indonesia ranks second after Singapore with the most significant number of obese adolescents, 12.2%, then Thailand (8%), Malaysia (6%) and Vietnam (4.6%) (Unicef, 2012). The emergence of nutritional problems in adolescents is basically due to wrong dietary behaviour, which is an imbalance between nutritional consumption and recommended nutritional adequacy. This research uses a descriptive-analytic design with a cross-sectional approach. The population was all students of class XI of SMA Negeri 3 Mataram, totalling 430 people. The sample was 86 people with simple random sampling technique. The variable used in this study is the level of student knowledge about obesity in adolescents. The data collection method uses a questionnaire that has tested for validity and reliability. Data analysis uses univariate analysis. The results showed that of the 86 respondents there were students with sufficient knowledge of 44 people (51.2%), most students aged 15-17 years were 74 people (86%), the majority of students were female, namely 57 people (66, 3%), and most students with average body mass index are 51 people (59.3%). Suggestion: students are expected to be able to increase their knowledge and control food intake both in the amount of food, type of food and frequency of meals to achieve the ideal BMI.